2022
DOI: 10.37680/scaffolding.v4i1.1253
|View full text |Cite
|
Sign up to set email alerts
|

Management of Teacher Competency Development in the Madrasah Ibtidaiyah Negeri

Abstract: The goal of this research was to examine the Planning of Teacher Competency Development in Madrasah Ibtidaiyah Negeri 1 Gunung Sitoli City, the Organizing of Teacher Competency Development in Madrasah Ibtidaiyah Negeri 1 Gunung Sitoli City, the Implementation of Teacher Competency Development in Madrasah Ibtidaiyah Negeri 1 Gunung Sitoli City, and the Monitoring of Teacher Compet The data collection technique used interviews, observations, and documentary studies, while the standard data validity suggested by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous research findings show competency development is one of them by conducting discussions, workshops, and training (Zebua et al, 2022). Another finding found that on-the-job training is the strategy for developing teacher competence (Sitorus et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Previous research findings show competency development is one of them by conducting discussions, workshops, and training (Zebua et al, 2022). Another finding found that on-the-job training is the strategy for developing teacher competence (Sitorus et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…The development of teacher competence begins with literature study, identifying, compiling, socializing, conducting standard tests, analyzing test results and determining teacher competence standards (Tang et al, 2020;Thomson et al, 2011). Teacher competence is very necessary because teachers play a strategic role, especially in forming character through the development of personality and desired values (Romijn et al, 2021;Zebua et al, 2022). Teachers also have duties and roles, including mastering and developing subject matter, planning and preparing daily lessons, controlling and evaluating activities of students (Muna et al, 2017;Romijn et al, 2021).…”
Section: Introductionmentioning
confidence: 99%